Evaluation of Under-utilized Fruit Tree Species in Hortipastoral System - Shukla, S.K.; Tewari, R.K.; Rai, P. (Indian Journal of Agroforestry, 2020)
A study was conducted during 1995 to 2001 at National Research Centre for Agroforestry, Jhansi, to evaluate the performance of twelve fruit tree species, viz. Emblica officinalis (Aonla), Buchanania lanzan (Chironji), Annona squamosa (Custard apple), Aegle marmelos (Bael), Cordia myxa (Lasora), Morus rubra (Red mulberry), Tamarindus indica (Tamarind), Punica granatum (Pomegranate), Achras zapota (Sapota), Manilkara hexandra (Khirni), Limonia acidissima (Kainth) and Ziziphus mauritiana (Deshi Ber) in hortipastoral system. The study revealed that the fruit trees namely, Emblica officinalis, Cordia myxa, Morus rubra and Ziziphus mauritiana proved hardy and precocious and could be grown successfully with satisfactory plant establishment, survival and growth in rangelands of semi-arid regions in association with natural vegetation, while the fruit species, viz. Buchanania lanzan, Annona squamosa and Achras zapota were not suitable for growing in hortipastoral system in rangelands because of their poor establishment and survival.